Interaction between endothelial injury and immune response in septic shock: from basic research to clinical applications - Wang, Yang; Guan, Qing-Nan; Zhang, Zhong-Jv; Zhang, Yu-Meng (Frontiers in Physiology, 2025)
Septic shock is a life-threatening condition caused by microorganisms and their toxins, which often results in severe haemodynamic instability and multi-organ dysfunction. Immune system dysfunction and endothelial injury play crucial roles in its pathogenesis and progression. In septic shock, pathogen recognition triggers immune activation, leading to excessive cytokine release and hyperactivation of immune cells. This overwhelming inflammatory response not only exacerbates endothelial injury, but also increases the risk of secondary infections, creating a vicious cycle that suppresses immune function and increases mortality. Cytokines alter the endothelial cell phenotype and structure, causing dysfunction, increased vascular permeability, and infiltration of inflammatory cells and cytokines into the interstitial space. The exposure of adhesion molecules promotes leukocyte migration and activation of coagulation pathways, significantly increasing the risk of thrombosis. These interactions contribute towards systemic oedema, hypotension, and microcirculatory dysfunction, exacerbating organ hypoxia and failure. This article explores the intricate interplay between endothelial injury and immune response in septic shock and its clinical implications. We highlight the potential of immunomodulation in mitigating immune damage as well as suppression. Additionally, we discuss endothelium-targeted therapies, including anti-inflammatory strategies, endothelial repair, and microcirculation improvement. Future research should focus on developing novel drugs and refining therapeutic approaches to effectively counteract endothelial damage and immune dysregulation, ultimately improving clinical outcomes and reducing morbidity and mortality.